Distortion of the Supervisory Function of the Village Consultative Body over Village Fund Management in Radda Village - Ilham Hidayat Azis; Aulia Khaerunnisa; Abdul Rahman Nur (SIGn Jurnal Hukum, 2026)
The mainstreaming of regional autonomy positions the BPD as an important institution for maintaining institutional checks and balances in village financial governance. In practice, this normative authority is connected to the sociological reality of the post-disaster area of Radda Village, which shows a weakening of the participatory supervisory function. This study aims to identify and analyze the implementation of the supervisory function of the BPD in budget management and to evaluate the institutional constraints that affect the effectiveness of that supervision. This study uses normative-empirical legal research to examine the gap between regulatory instruments and their implementation in the field. The findings show that the digitalization of financial recording through an administrative system is not sufficient to ensure substantive compliance in the implementation of physical development programs. The internal supervision of the BPD remains weakened by low administrative legal literacy and limited technical understanding among its members. This condition allows unilateral action by the Village Head in modifying programs without formal deliberation, so that the supervisory function of the BPD tends to be limited to retrospective supervision. This study recommends strengthening the regulatory capacity of the BPD through administrative law education, technical budget verification training, and regional policy support to restore the internal supervisory function in accountable village governance.